195The Health4Life Initiative: An eHealth intervention targeting multiple lifestyle risk behaviours among Australian adolescents. (2nd September 2021) - Gardner, Lauren; Champion, Katrina; Teesson, Maree; Newton, Nicola; Kay-Lambkin, Frances; Chapman, Cath; Thornton, Louise; Slade, Tim; Mills, Katherine; Sunderland, Matthew; Allsop, Steve; Hides, Leanne; et al.
Abstract: Background: Physical inactivity, poor diet, sedentary recreational screen time, poor sleep, alcohol use and smoking (the "Big 6") are key lifestyle risk factors for chronic disease. The Big 6 typically emerge during adolescence, co-occur and continue into adulthood. To improve short- and long-term health, early and effective prevention is critical. Methods: A cluster randomised controlled trial (ACTRN12619000431123) is being conducted in 71 schools across NSW, QLD and WA. Schools are randomised to the Health4life intervention or health education as usual. The intervention has three components: 1) An online, school-based program delivered to all Year 7 students; 2) An accompanying smartphone application (all students); 3) Booster content, delivered to at-risk students in Years 8 and 9. Students complete questionnaires on five occasions over three years. Results: Preliminary analyses including 6716 students (49% female) indicated that 22% of participants met national guidelines for physical activity, 27% reported drinking 2+ cups of sugar-sweetened beverages/week, 3% had consumed a standard alcoholic drink in the prior 6 months, 2% had tried smoking, 86% engaged in excessive recreational screen time, and 32% had inadequate sleep. The final dataset will be analysed for the conference. Conclusions: Many Australian adolescents are engaging in lifestyle behaviours that put them at risk of chronic disease. Effective and scalable preventive interventions that simultaneously target these behaviours are needed. Key messages: This is the first trial of an eHealth intervention to concurrently target the Big 6 among adolescents. Health4Life has the potential to improve physical and mental health in adolescence and beyond.